Reduced impact of nonverbal cues during integration of verbal and nonverbal emotional information in adults with high-functioning autism - Pelzl, Michael Alexander; Travers-Podmaniczky, Gabrielle; Brück, Carolin; Jacob, Heike; Hoffmann, Jonatan; Martinelli, Anne; Hölz, Lea; Wabersich-Flad, Dominik; Wildgruber, Dirk (Frontiers in Psychiatry, 2023)
Background: When receiving mismatching nonverbal and verbal signals, most people tend to base their judgment regarding the current emotional state of others primarily on nonverbal information. However, individuals with high-functioning autism (HFA) have been described as having difficulties interpreting nonverbal signals. Recognizing emotional states correctly is highly important for successful social interaction. Alterations in perception of nonverbal emotional cues presumably contribute to misunderstanding and impairments in social interactions. Method: To evaluate autism-specific differences in the relative impact of nonverbal and verbal cues, 18 adults with HFA (14 male and four female subjects, mean age 36.7 years (SD 11.4) and 18 age, gender and IQ-matched typically developed controls (14 m/4f, mean age 36.4 years (SD 12.2)) rated the emotional state of speakers in video sequences with partly mismatching emotional signals. Linear regression coefficients (-values) were calculated as a measure of the reliance on the nonverbal and verbal components of the videos for each participant. Regression coefficients were then compared between groups to test the hypothesis that autistic adults base their social evaluations less strongly on nonverbal information. Further exploratory analyses were performed for differences in valence ratings and response times. Results: Compared to the typically developed control group, nonverbal cue reliance was reduced in adults with high-functioning autism (t (23.14) = -2.44, p = 0.01 (one-sided)). Furthermore, the exploratory analyses showed a tendency to avoid extreme answers in the HFA group, observable via less positive as well as less negative valence ratings in response to emotional expressions of increasingly strong valence. In addition, response time was generally longer in HFA compared to the control group (F (1, 33) = 10.65, p = 0.004). Conclusion: These findings suggest reduced impact of nonverbal cues and longer processing times in the analysis of multimodal emotional information, which may be associated with a subjectively lower relevance of this information and/or more processing difficulties for people with HFA. The less extreme answering tendency may indicate a lower sensitivity for nonverbal valence expression in HFA or result from a tendency to avoid incorrect answers when confronted with greater uncertainty in interpreting emotional states.